Perhitungan Beban Pencemaran Air Sungai Cibabat Kota Cimahi Provinsi Jawa Barat - Mochammad Azhar Rais Alfaroby; Eka Wardhani (Fakultas Teknik, 2021)
The lack of domestic wastewater management services in the Cibabat River Basin has resulted in the Cibabat River being a place to collect domestic wastewater. This of course can reduce water quality as well as reduce the function of the river itself. The Cibabat river is known to be a sub-watershed of the Citarum River with a surface area of 1,855 km2. Activities in the Cibabat watershed contribute to the pollution load that causes the water quality of the Cibabat River to decline, which of course has an impact on the decrease in the quality of the river and increase in the polluting load that the river will receive. The research method uses the calculation of the pollutant load based on Permen LH 115/2003. The data used are secondary data from DLH Cimahi City, which conducted a water quality analysis at three points during three different seasons in 2019. One of the steps to overcome and control the pollution that occurs is to determine the actual pollutant load so that it can easily determine the application of effective technology for controlling river water pollution in the Cibabat River at theCimahi City.